2015
DOI: 10.1038/srep16623
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation of Myostatin Mutations in Pigs Using the CRISPR/Cas9 System

Abstract: Genetically modified pigs are increasingly used for biomedical and agricultural applications. The efficient CRISPR/Cas9 gene editing system holds great promise for the generation of gene-targeting pigs without selection marker genes. In this study, we aimed to disrupt the porcine myostatin (MSTN) gene, which functions as a negative regulator of muscle growth. The transfection efficiency of porcine fetal fibroblasts (PFFs) was improved to facilitate the targeting of Cas9/gRNA. We also demonstrated that Cas9/gRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 42 publications
(50 reference statements)
5
108
0
Order By: Relevance
“…While mouse models have been widely used, the CRISPR/Cas9 gene editing approach has been established in many other animal models including worm [84], fly [85], fish [86, 87], rat [88], rabbit [89, 90], goat [91], sheep [92], dog [93], pig [94], and monkeys [95]. The expansion of transgenic animal models beyond mouse is advantageous to biomedical research that accelerates the development of new therapeutic strategies.…”
Section: Applications Of Crispr/cas9 For Cell Biological Studiesmentioning
confidence: 99%
“…While mouse models have been widely used, the CRISPR/Cas9 gene editing approach has been established in many other animal models including worm [84], fly [85], fish [86, 87], rat [88], rabbit [89, 90], goat [91], sheep [92], dog [93], pig [94], and monkeys [95]. The expansion of transgenic animal models beyond mouse is advantageous to biomedical research that accelerates the development of new therapeutic strategies.…”
Section: Applications Of Crispr/cas9 For Cell Biological Studiesmentioning
confidence: 99%
“…Prather’s group has created pigs with substantial immunity to PRRSv virus by knocking out the PRRSv receptor with random NHEJ [33]. Others have, for instance, knocked out myostatin in pigs [34]. The Roslin institute, the original developers of cloning and one of the great pioneers in this field, have in one of the first examples of use of homologous recombination in large animals, changed a pig allele to a warthog allele to induce resistance to African Swine Fever virus [35].…”
Section: Modern Genome Editing Methodsmentioning
confidence: 99%
“…For example, designed mega-nucleases can induce double-stranded breaks (DSBs) at specific sites in the genome, resulting in random modifications through non-homologous end joining (NHEJ) [1113]. Recent achievements in the use of mega-nucleases such as Zinc-finger nucleases (ZFNs) [11, 12], transcription activator-like effector nucleases (TALENs) [1416], and CRISPR/Cas9 [17] have also suggested that KO pigs can be efficiently generated. Recently, we and other groups have described X-linked or autosomal SCID-like pigs that were created by disrupting interleukin 2 receptor gamma (IL2RG) [18, 19], autosomal Rag-1/2 [20], and RAG-2 SCID [21] or by natural breeding [22].…”
Section: Introductionmentioning
confidence: 99%